This study aims to analyze the influence of leadership, organizational culture, and education and training on employee performance at Sekolah Tinggi Ilmu Manajemen Kosgoro (STIMA Kosgoro), Jakarta. The research employs both descriptive and inferential sta - Kamarul Zaman Rambe (Privietlab, 2022)
This study aims to analyze the influence of leadership, organizational culture, and education and training on employee performance at Sekolah Tinggi Ilmu Manajemen Kosgoro (STIMA Kosgoro), Jakarta. The research employs both descriptive and inferential statistical approaches. Primary data were collected through structured questionnaires distributed to 60 lecturers and employees of STIMA Kosgoro. The results of the study indicate that leadership is perceived positively by respondents, with agreement levels averaging 51.25% for leadership traits, 45.85% for leadership functions, 45.8% for leadership intelligence, and 50.7% for leadership competence. This suggests that leadership within the institution is generally considered effective in terms of characteristics, functions, and competencies. Organizational culture is also perceived positively, with agreement levels averaging 48.6% for individual initiative and 44.9% for integration. These findings indicate that organizational culture has successfully encouraged coordination, responsibility, and effective work planning among employees. Education and training are perceived as highly positive, with agreement levels averaging 65% for educational aspects and 63.3% for training activities. These programs have contributed to improving employee skills, knowledge, and work performance. Employee performance is also considered good, with agreement levels averaging 60.7% for work achievement and 52.2% for work motivation. This reflects employees’ ability to complete tasks effectively, demonstrate responsibility, and maintain high motivation levels. The results further reveal that leadership is the most dominant variable influencing employee performance, contributing 48.80%, followed by education and training (46%), and organizational culture (33.50%). Overall, leadership, organizational culture, and education and training have a positive and significant influence on employee performance. This study concludes that improving leadership quality, strengthening organizational culture, and enhancing education and training programs are essential strategies to improve employee performance in higher education institutions.